The Crime Of Online Gambling In The Slots Type Among Teenagers In A Social Practice That Contradicts Article 303 Of The KUHP (Case Study In Karawang District) - Adhamianda, Ragha; Hidayat, Anwar; Abas, M (Universitas Muhammadiyah Sumatera Utara, 2024)
Modern era advances encourage advances in internet technology providing benefits to society. Everything in electronic media can be accessed freely by the general public. On the other hand, advances in internet-based electronic media can also have negative impacts, such as the rise of new issues in society, especially the rise of online gambling cases. Online gambling refers to a type of betting activity in which participants place bets against each other using money as a betting tool chosen by online players and gamblers and carried out using electronic media connected to the internet. In this problem in Karawang district, online gambling is very widespread among teenagers and has a bad impact on users who gamble online. The role of law enforcement officials must be to participate in helping and following up on problems that are already circulating in the community. Online gambling violates laws and social conventions, as well as moral principles. As a result, anyone involved in internet gambling must face severe criminal penalties. Article 303, Article 303 bis of the Criminal Code, Article 2 paragraphs (1), (2), and (3) of Law Number 7 of 1974 concerning Gambling, and Article 27 paragraph 2 Jo. Article 45 paragraph 2 of the ITE Law contains provisions that regulate criminal acts for online gambling players in Indonesia